PERENCANAAN PERSEDIAAN BAHAN BAKU KEDELAI MENGGUNAKAN METODE EOQ DI CV. PQR - Akhsani Nur Amalia (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2023)
This study aims to determine the inventory planning of Soybean raw materials to produce Tempe products. The analysis was carried out based on the need for Soybean raw materials for the past 12 months. Raw material inventory planning is carried out using the Economic Order Quantity (EOQ) method. Where, the lead time is known with certainty and the arrival of Soybean raw materials at once. The results showed that the optimal order quantity of Soybeans in one order was 3117.31 kg. Soybean raw material ordering is carried out every seven days and eight hours. The minimum amount of Soybean inventory in the warehouse is 978.56 kg. Based on these points, the total cost of Soybean raw material inventory is Rp 176,287,365.